2015
DOI: 10.1007/s12672-015-0219-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thyroid Cancer Cell Lines in Murine Orthotopic and Intracardiac Metastasis Models

Abstract: Thyroid cancer incidence has been increasing over time, and it is estimated that ~1950 advanced thyroid cancer patients will die of their disease in 2015. To combat this disease, an enhanced understanding of thyroid cancer development and progression as well as the development of efficacious, targeted therapies are needed. In vitro and in vivo studies utilizing thyroid cancer cell lines and animal models are critically important to these research efforts. In this report, we detail our studies with a panel of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
1
29
1
Order By: Relevance
“…The CUTC60 cells readily formed orthotopic and flank tumors in nude mice, demonstrating lung metastases in the orthotopic model. Interestingly, the CUTC48 cells did not form tumors in any mouse model that we tested, including the NRG mice, which is consistent with the take rate we and others have observed with the RET/PTC1-expressing TPC1 cells (34,45,46). Our previous studies have indicated that thyroid cancer cell lines with the highest take rate harbor mutations in BRAF V600E (34), thus indicating that the RET/PTC1-expressing cells may exhibit an overall less aggressive phenotype.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The CUTC60 cells readily formed orthotopic and flank tumors in nude mice, demonstrating lung metastases in the orthotopic model. Interestingly, the CUTC48 cells did not form tumors in any mouse model that we tested, including the NRG mice, which is consistent with the take rate we and others have observed with the RET/PTC1-expressing TPC1 cells (34,45,46). Our previous studies have indicated that thyroid cancer cell lines with the highest take rate harbor mutations in BRAF V600E (34), thus indicating that the RET/PTC1-expressing cells may exhibit an overall less aggressive phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…All animal studies were conducted in accordance with the animal protocol procedures approved by the Institutional Animal Care and Use Committee (IACUC) at the University of Colorado Denver (Aurora, CO). Athymic nude mice [Hsd:Athymic Nude-Foxn1 nu (069) from Envigo or in-house breeding for the CUTC60 and CUTC61 cells], SCID/Beige mice (C.B-17/IcrHsd-Prkdc scid Lyst bg-J from Envigo), or NRG mice [NOD.Cg-Rag1 tm1Mom Il2rg tm1Wjl /SzJ (#007799) from The Jackson Laboratory] were anesthetized with tribromoethanol (250 mg/kg), and the indicated thyroid cancer cells (5 Â 10 5 in a 5 mL cell suspension) were injected into the right thyroid gland with the aid of a dissecting microscope (Nikon SMZ645), and the skin closed with staples, as described previously (33)(34)(35). Growth was monitored for the indicated days.…”
Section: Orthotopic Mouse Modelmentioning
confidence: 99%
“…We next evaluated the role of FAK kinase activity versus expression in tumor establishment and growth using the orthotopic thyroid cancer model (9,3438). To assess the role of FAK kinase activity, BCPAP or 8505C cells engineered to stably express a luciferase-IRES-GFP plasmid were injected into the right thyroid gland of athymic nude mice, as previously described (9).…”
Section: Resultsmentioning
confidence: 99%
“…While the xenograft models are quite straightforward in that the cells grown and collected are injected into the subcutaneous tissues of immunocompromised mice, the orthotopic model is more complex to establish, since it requires a microsurgical procedure to directly place the cells into one or both the thyroid lobes [ 32 , 33 , 34 ]. Nonetheless, since the development of such a model [ 35 ], orthotopic implantation has been widely adopted to study the genetic and bio-molecular patterns of thyroid carcinogenesis [ 9 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Mouse Models Of Thyroid Cancersmentioning
confidence: 99%
“…Recently, our group developed a high-frequency ultrasound (HFUS) guided procedure for the orthotopic implantation of FTC cells, demonstrating its feasibility and comparing tumor growth curves with the standard surgical procedure, showing interesting results (see below) [ 34 ]. In any case, the main limitations of such in vivo models are the use of mice with various degrees of immunodeficiency, which precludes studying the interactions between the cancer cells and the host immune system [ 42 ] and hence the ability to predict the efficacy of clinical therapeutics.…”
Section: Mouse Models Of Thyroid Cancersmentioning
confidence: 99%